Hawaiian ways of Protection: acting for self-determined Indigenous futurities - Jean-Marc Serme (European Journal of American Studies)
This article means to explicate the notion of Protection claimed explicitly by the Kia`i, the Guardians or Protectors, of the Mauna Kea summit against the infringement of the TMT project. We must understand how their historical relationship to the land connects Kanaka Protectors to their kuleana, their sphere of responsibility and continual maintenance of its health and bounty. Relationality and a worldview based on a continuum of connections between the universe at large, the land, non-humans and humans is the main framework that allows us to understand not only the actions, but the vocabulary and the mindset in which Hawaiian Protection movements articulate their spiritual and political positions as well as their visions of the future.